2011
DOI: 10.1002/jat.1656
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function alteration of hemoglobin in arsenicosis patients: a probable pathway to exert toxicity

Abstract: Chronic arsenicosis, a major public health concern in India and Bangladesh, is mainly caused by ingestion of arsenic (As) contaminated ground water. Although this problem has been studied extensively, the mechanism of toxicity remains unknown. This paper investigates the process of trivalent arsenicals binding to hemoglobin (Hb) in chronic arsenicosis patients and consequent modification in the structure-function activity of Hb. In this work peroxidase activity, thermal denaturation profile, oxygen releasing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Binding of arsenicals with blood proteins can be a critical issue in arsenic speciation in blood. It may alter arsenic metabolism and distribution, and consequently lead to changes in arsenic bioavailability and the kinetics of accumulation and excretion, as well as the function of proteins . For example, transferrin in plasma can reportedly bind to inorganic arsenic instead of methylated arsenic. , A ternary dimethylarsinous-hemoglobin–haptoglobin complex was also detected in rat plasma .…”
Section: Discussionmentioning
confidence: 99%
“…Binding of arsenicals with blood proteins can be a critical issue in arsenic speciation in blood. It may alter arsenic metabolism and distribution, and consequently lead to changes in arsenic bioavailability and the kinetics of accumulation and excretion, as well as the function of proteins . For example, transferrin in plasma can reportedly bind to inorganic arsenic instead of methylated arsenic. , A ternary dimethylarsinous-hemoglobin–haptoglobin complex was also detected in rat plasma .…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that arsenic induces oxidative damage to human erythrocytes producing anemia-related changes including alterations in shape, deformability, agreeability, and osmotic fragility (Bollini et al, 2010). Studies in human populations highly exposed to arsenic in drinking water also reported structural and functional hemoglobin and erythrocyte alterations due to oxidative stress, and as a result, diminished oxygen binding affinity (Mondal et al, 2012) and premature cell death (Biswas et al, 2008), alterations likely to lead to clinical anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Hb is rich in -SH groups and it is suggested that arsenic and its metabolites may have a propensity to bind to Hb and reduce its binding affinity to oxygen. Recently, Mondal et al [11] studied the binding affinity of trivalent arsenic to Hb and its consequential modification of the structure and function of Hb. Isolated Hb from arsenicosis patients had a binding affinity constant of 0.256 μM −1 with a Hill coefficient of +2.961, suggesting that arsenic molecules modify and lower the binding affinity to oxygen.…”
Section: Erythrocytesmentioning
confidence: 99%